Internal consistency of the scales of the Chinese version of the questionnaire «Affective and motivational orientation related to erotic arousal» - Fourmanov, Igor A.; Xinchun Nie, (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
Understanding various sexual motives has a profound impact on determining the causes, significance and consequences of sexual behaviour. The article presents the procedure for adapting the Chinese version of the questionnaire «Affective and motivational orientation related to erotic arousal» and empirically established its reliability by the criterion of internal consistency. Gender differences in hierarchies and the strength of dispositional sexual motives of the Chinese were also revealed: women differ in the greater strength of the motives of comfort, power, care and self-importance, and men – in the greater strength of the motives of the importance of a partner, pleasure, submission and procreation.
Keywords: sexual motivation; reliability; internal consistency